2014
DOI: 10.1155/2014/931269
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Phenolics Extracted from Idesia polycarpa Defatted Fruit Residue and Its Antioxidant and Depigmenting Activity In Vitro and In Vivo

Abstract: Extraction of phenolics from Idesia polycarpa defatted fruit residue was optimized by the maximization of the yield in total phenolics, using the response surface methodology. The optimized conditions were 50% ethanol, 5 h extraction time, 1 : 40 liquid to solid ratio, and 80°C extraction temperature. The experimental average total phenolics yield was 54.49 ± 4.26 mg/g. These antioxidant properties of phenolics were comprehensively analyzed for the first time. All the extracts not only demonstrated the signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The relative report has been confirmed that the oil of its fruits is nontoxic and has anticarcinogenic and antidiabetic effects and antihypertensive properties [ 12 , 13 ]. Moreover, flavonoid and phenolic glycosides of I. polycarpa exhibited various biological activities, such as antioxidant, skin whitening, inhibition of platelet aggregation, and antiadipogenesis [ 14 ]. Previous researches demonstrated that the ethyl acetate extracts of I. polycarpa exhibited strong antioxidant [ 14 ], anti-inflammatory, and whitening activities in vitro and in vivo [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The relative report has been confirmed that the oil of its fruits is nontoxic and has anticarcinogenic and antidiabetic effects and antihypertensive properties [ 12 , 13 ]. Moreover, flavonoid and phenolic glycosides of I. polycarpa exhibited various biological activities, such as antioxidant, skin whitening, inhibition of platelet aggregation, and antiadipogenesis [ 14 ]. Previous researches demonstrated that the ethyl acetate extracts of I. polycarpa exhibited strong antioxidant [ 14 ], anti-inflammatory, and whitening activities in vitro and in vivo [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…There have been several studies on Idesia polycarpa fruit, including functional research on Idesia polycarpa fruit extraction and studies on the improvement of the extraction process. The remarkable antioxidant qualities, anti-skin-aging ability (3) and anti-adipogenic ability (4) of Idesia polycarpa extracts have been demonstrated, and an optimized extraction method has also been established (5). However, reports on the application of Idesia polycarpa fruit for the other purposes are still limited.…”
Section: Introductionmentioning
confidence: 99%